Methane Inhalation Protects Against Lung Ischemia-Reperfusion Injury in Rats by Regulating Pulmonary Surfactant via the Nrf2 Pathway - Zhang, Bing; Tian, Xiaojun; Li, Guangqi; Zhao, Han; Wang, Xuan; Yin, Yanwei; Yu, Junmin; Meng, Chao (Frontiers in Physiology, 2021)
Methane (CH4) exerted protective effects against lung ischemia-reperfusion (I/R) injury, but the mechanism remains unclear, especially the role of pulmonary surfactant. Therefore, this study aimed to explore the effects of CH4 inhalation on pulmonary surfactant in rat lung I/R injury and to elucidate the mechanism. Rats were randomly divided into 3 groups (n = 6): the sham, I/R control and I/R CH4 groups. In the sham group, only thoracotomy was performed on the rats. In the I/R control and I/R CH4 groups, the rats underwent left hilum occlusion for 90 min, followed by reperfusion for 180 min and ventilation with O2 or 2.5% CH4, respectively. Compared with those of the sham group, the levels of large surfactant aggregates (LAs) in pulmonary surfactant, lung compliance, oxygenation decreased, the small surfactant aggregates (SAs), inflammatory response, oxidative stress injury, and cell apoptosis increased in the control group (P < 0.05). Compared to the control treatment, CH4 increased LA (0.42 ± 0.06 vs. 0.31 ± 0.09 mg/kg), oxygenation (201 ± 11 vs. 151 ± 14 mmHg), and lung compliance (16.8 ± 1.0 vs. 11.5 ± 1.3 ml/kg), as well as total antioxidant capacity and Nrf2 protein expression and decreased the inflammatory response and number of apoptotic cells (P < 0.05). In conclusion, CH4 inhalation decreased oxidative stress injury, inflammatory response, and cell apoptosis, and improved lung function through Nrf2-mediated pulmonary surfactant regulation in rat lung I/R injury.